Metodología del aula invertida (flipped clasroom) en el proceso de enseñanza-aprendizaje de matemática de la unidad educativa José María Velasco Ibarra cantón Buena Fe periodo 2021 - Nájera Sánchez , Gustavo Fabrizzio (2021)
The present research work entitled: "FLIPPED CLASSROOM METHODOLOGY (FLIPPED CLASSROOM) IN THE TEACHING LEARNING PROCESS OF MATHEMATICS", is important because at present it is sought that the student assumes responsibility for their own learning and in the classroom has the ability to perform adequately, The general objective of the project is to determine the importance of the implementation of the flipped classroom methodology (flipped classroom) in the process of teaching and learning mathematics in the students of the first year of high school accounting "A" of the José María Velasco Ibarra Educational Unit, period 2020-2021, The approach of this research is mixed qualitative and quantitative; The latter refers to the collection of numerical data on the variables to be investigated, in addition to the fact that it allows to study and quantify it. It is also qualitative because an interview will be conducted with the area teacher in which data, characters, attributes or non-quantifiable faculties were obtained